MILITARY INVOLVEMENT IN POLITICS: A PRELUDE TO SABOTAGE BEHAVIOURS AND MUTINY - Anyaegbunam, Michael C; Okonkwo, Kizito I; Anekwe, Sebastine (Practicum Psychologia, 2018)
Military government emerge through violent seizure of power from an elected government, they suspend all hitherto legitimate arms and processes of government when they succeed. Sabotage, the wilful and malicious disruption of the normal processes and function of the nation with respect to national defense, and mutiny, the act of refusing to obey the orders of authority seem to be the aftermaths of military intervention in politics since this jeopardized their professionalism. This position is supported by the MODE theory which explained that love for power, and wealth (slave mentality) is an attitudinal disposition among Nigeria elites both civilian and military, which predisposes them to Machiavellians unscrupulousness. If the military would be supported with increased funding to enable them purchase efficient weapons and obtain correct training and motivation, sabotage behavior that fuel insurgency will be curtailed.